Humanizing delivery: progress and difficulties for its implementation - Almeida, Samira Maria Oliveira; Silveira, Maria de Fátima (Revista de Enfermagem UFPE on line, 2009)
Objective: to identify the advances and difficulties in implementation and practice of humanization of parturition. Methodology: the study was conducted in a qualitative approach, and its sample was composed of 13 professionals directly involved with the care. Data were collected through semi-structured interview guide and observation from the participants. Processing of data, using the content analysis ― themes analysis. Results: advances in the process of humanization are considered least in comparison to the difficulties raised by the interviewees. The study has been approved by the Committee of Ethics in Research of the University of Paraiba State (CAAE – 0724.0.000.133-06). The resistance of professionals, the limited of the vacancies, high demand, accompanied by the small number of professionals, are the factors considered most difficult in the practice of humanization. Conclusion: the results show that the factors related to the difficulties and advances in humanization depend largely on professionalism and ethics on the attitude of managers and health professionals involved with care delivery, so that together can overcome the obstacles that put forward to humanized care in all its dimensions. Descriptors: women's health, parturition, humanization.